Liberate Hong Kong? Language, agency, and imagining political futures - Wong, Ka Hang (Teaching English as a Foreign Language Journal, 2025)
The slogan “Liberate Hong Kong, revolution of our times” (光復香港，時代革命) emerged during the 2019 protests as a symbol of solidarity and political aspiration among Hongkongers. Its prominence and subsequent criminalization highlight its role in debates over identity, governance, and self-determination. This article examines the discursive function of the slogan and its pedagogical implications within Critical English for Academic Purposes (CEAP), showing how language can challenge state narratives while fostering civic engagement. Using documentary analysis, the study combines Critical Discourse Analysis (CDA) with CEAP to trace the slogan’s role as a discursive act, drawing on political addresses, policy responses, and exiled initiatives. Findings indicate that the slogan operates as a counter-discourse to the Chinese Communist Party’s (CCP) reunification narrative. It constructs political agency and solidarity among participants. It also shapes imaginaries of political transformation, reflected in diasporic activism and proposals for alternative governance. By integrating CDA and CEAP, the study highlights the slogan’s dual political and pedagogical significance, demonstrating how language learning can intersect with civic imagination to promote critical engagement with governance, agency, and self-determination. Overall, the analysis underscores the interdisciplinary reach of applied linguistics and the capacity of discourse to enact social critique and envision political possibilities.